القرآنية في شعر رضا الخفاجـي مجموعة (( كربائيلو )) نموذجاً - , م.د فاضل حمد مكوار (Thi Qar Arts Journal, 2021)
This study aims at  finding  out the effects of the miraculous  text of the Holy Quran with  its construction, contents, indications, significance  ,  allusions, and its explicitly  in the new textual construction through employing  vocabularies , and the Qur’anic structure directly, whether it is in its  conformity or not without any modifications; or indirectly accompanied by indicative and illusionistic  modification by absorbing the text  in a new structural environment,  then discovering the reference it descends from . This is due to the  great role that the Qur’anic system plays in the context of the creative image in prose and poetry. The study limits itself  to the poetic output of the poet Reda Al-Khafaji through one model, of  his poetic collection “Karbalaio  Beit Al-Rab” which depicts the painful incident of Al-Taff, and the holy city of Karbala, with all its events and characters through a significant  reference to the Qur’anic text from which the poetry of this poet is called for  , prepared and consulted